2016
DOI: 10.1177/0306624x15596728
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Challenging Skills in Work With Young Offenders

Abstract: Probation officers and others who work with young offenders often challenge or confront their clients in relation to pro-criminal comments and criminal behaviour. There is, however, very little research that can inform practitioners about which forms of challenging most effectively engage young people. This study examines the use of challenging by youth justice workers in New South Wales, Australia. Researchers observed and audiotaped 116 interviews between youth justice workers and their clients with a view t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Among the best known of these have been Bonta’s STICS study in Canada, which used a random allocation design to compare reconviction rates after supervision by officers who had received additional training in evidence-based practice skills with reconvictions after supervision by officers who had not received the training (Bonta et al, 2011); Trotter’s continuing series of studies of the impact of particular practice skills (e.g. Trotter 2013, 2017); Taxman’s (2008) study of the effects of training in ‘proactive community supervision’, and the STARR study (Robinson et al, 2012) that looked at the impact of skills on re-arrest rates. The quasi-experimental Jersey Supervision Skills Study (JS3) identified a range of skills used by probation staff in videotaped interviews and found significantly lower reconviction rates among people supervised by more skilled staff (Raynor et al, 2014).…”
Section: Shifting the Focus From Programmes To Skillsmentioning
confidence: 99%
“…Among the best known of these have been Bonta’s STICS study in Canada, which used a random allocation design to compare reconviction rates after supervision by officers who had received additional training in evidence-based practice skills with reconvictions after supervision by officers who had not received the training (Bonta et al, 2011); Trotter’s continuing series of studies of the impact of particular practice skills (e.g. Trotter 2013, 2017); Taxman’s (2008) study of the effects of training in ‘proactive community supervision’, and the STARR study (Robinson et al, 2012) that looked at the impact of skills on re-arrest rates. The quasi-experimental Jersey Supervision Skills Study (JS3) identified a range of skills used by probation staff in videotaped interviews and found significantly lower reconviction rates among people supervised by more skilled staff (Raynor et al, 2014).…”
Section: Shifting the Focus From Programmes To Skillsmentioning
confidence: 99%
“…On a practical level, educational fathering programs (used here as a differentiation from other supported/visiting services) differ in length, number of participants and content (for more, see Block et al, 2014;Meek, 2007). Relationships and facilitator skills are pivotal in the delivery of these programs (LaRosa and Rank, 2001;Meek, 2007), a factor acknowledged in broader research into effective practice with involuntary clients (see Trotter et al, 2017). Results from several UK evaluations of prison fathering programs indicate that content worked when participants were given the opportunity to suggest topics (Meek, 2007;Meek and Baumer, 2016); content was thus tailored to the needs of each group.…”
Section: Educational Fathering Programsmentioning
confidence: 99%
“…As well as England, Scotland and Wales there were participants from Australia, Canada and the island of Jersey. We were aware of Trotter’s well established and continuing work in this field (see, for example, Trotter, 1996; Trotter and Evans, 2012; Trotter et al, 2017), and of the beginning of the STICS study in Canada (‘Strategic Training Initiative in Correctional Supervision’: Bonta et al, 2011); we also discussed the early stages of the Jersey Supervision Skills Study (JS3; Raynor et al, 2014b; Ugwudike et al, 2014) and we tried also to incorporate insights from desistance theories (Maruna and LeBel, 2010) and ‘good lives’ models (Ward, 2010).…”
Section: The Last Decade (Approximately)mentioning
confidence: 99%